Maximum efficiency solution for capacitive wireless power transfer with N receivers. Issue 1 (19th March 2020) - Minnaert, Ben; Mongiardo, Mauro; Costanzo, Alessandra; Mastri, Franco
Abstract: Typical wireless power transfer (WPT) systems on the market charge only a single receiver at a time. However, it can be expected that the need will arise to charge multiple devices at once by a single transmitter. Unfortunately, adding extra receivers influences the system efficiency. By impedance matching, the loads of the system can be adjusted to maximize the efficiency, regardless of the number of receivers. In this work, we present the analytical solution for achieving maximum system efficiency with any number of receivers for capacitive WPT. Among others, we determine the optimal loads and the maximum system efficiency. We express the efficiency as a function of a single variable, the system kQ-product and demonstrate that load capacitors can be inserted to compensate for any cross-coupling between the receivers.